Pacing and Positioning Strategies During an Elite Fixed-Gear Cycling Criterium - Nicolas Babault; Christos Paizis; Mary Trimble; David A. Trimble; Carole Cometti (Frontiers Media S.A., 2020)
Fixed-gear cycling performance during criteriums predominantly involves the aerobic system. Whether pacing is another important factor for performance is unknown. The purpose of the present study was to explore pacing and/or positioning strategies of fixed-gear riders during criteriums. Race results of an international fixed-gear criterium were analyzed (20 laps for women and 28 laps for men; laps = 1,270 m). Statistics were conducted on individuals lap time and positioning during the finals. Race pattern in women (n = 35) and men (n = 53) revealed that the faster laps (P < 0.05) were in the middle and at the end of the race and the slower laps (P < 0.05) were at the end of the race (laps 17-18 for women and lap 26 for men). The final ranking was significantly correlated with the mean race position (Kendall's tau = 0.664 and 0.689 for women and men, respectively). A coefficient of variation >50% revealed an important positioning variability. The best riders are mostly amongst the first during the race. However, the others exhibited larger mean position variations during the first half of the race. Our results demonstrated variable pacing strategies during fixed-gear criteriums. Although some riders had economical drafting strategies during the first half of the race, riding placed ahead during the whole race seemed to be an essential performance factor.